Phenotypic and genotypic characterization of virulence markers and antifungal susceptibility of oral Candida species from diabetic and non-diabetic hemodialysis patients - Mohammadi, Faezeh; Charkhchian, Maliheh; mirzadeh, Monirsadat (BMC oral health, 2023)
Patients with chronic kidney disease undergoing hemodialysis are often colonized by Candida species with high possibility of fungal infections. The purposes of this study were to determine the prevalence of Candida species, evaluate antifungal susceptibility profile, biofilm formation, proteinase and phospholipase activities, and the frequency of virulence genes in the Candida species isolated from the oral mucosa of hemodialysis diabetic (DM) and non-diabetic (non-DM) patients. This study identified several species of Candida isolated from 69 DM and 58 non-DM patients on hemodialysis using phenotypic methods and PCR-RFLP technique. The identification of C. albicans and C. glabrata complex was performed by HWP1 gene and four oligonucleotides (UNI-5.8S, GLA-f, BRA-f, and NIV-f), respectively. Antifungal susceptibility to amphotericin B, fluconazole, itraconazole, voriconazole, and caspofungin was assessed according to CLSI M27-A3/S4. The biomass, metabolic activity of biofilm, proteinase (P ), phospholipase (P ), and molecular study for virulence genes were assessed using crystal violet, XTT assay, agar-based hydrolytic enzyme, and PCR technique, respectively. Candida prevalence was 44.9% with 47.8% and 41.4% among DM and non-DM patients, respectively (P = .045). The species identified were C. albicans (49.5%), C. glabrata (16.5%), C. tropicalis (12%), C. kefyr (8.8%), C. parapsilosis (6.6%), C. dubliniensis (3.3%), and C. lusitaniae (3.3%). The antifungal susceptibility profile showed that all Candida isolates were sensitive to amphotericin B, itraconazole, voriconazole, and caspofungin whereas fluconazole resistance was observed in 6.3% (MIC ≥ 64 μg/mL) of C. albicans and 6.6% of C. glabrata (MIC ≥ 64 μg/mL). The susceptible- dose-dependent rate was found in 10.5% of C. albicans. The P values of C. albicans ranged from 0.37 to 0.66 for the DM and 0.44-0.73 for the non-DM group (P < 0.05). The non-albicans Candida (NAC) species produced higher degree of biomass and metabolic activity compared to C. albicans (P < 0.05). Furthermore, significant (p < 0.05) correlations were detected between the biofilm formation with P values and fluconazole MICs. The most detected virulence factors were ALS3 and Sap5. These results showed the importance of prevalence of NAC species in hemodialysis patients. Investigating antifungal susceptibility profile made a better understanding of the role of virulence markers in the pathogenesis of Candida strains.